ANALYSIS FACILITIES PEDESTRIAN AND BICYCLE LANE LANES AS FACILITIES MODA TRANSPORTATION PUBLIC OF INTEGRATION IN BEKASI KOTA - Karlinda, Dea Ayu; Rulhendri, Rulhendri; Murtejo, Tedy (ASTONJADRO, 2022)
Analysis facilities pedestrian and bicycle lanes as facilities integration modes of public transport in the city of bekasi (Case Study: Bekasi Terminal and BTC Bus Stop). The city of bekasi located in west java province which has an area of areas 210,49 km2. The city central being as business and commerce , and activities services so that be an attraction for newcomers to look for a job and to shelter  Terminal bekasi and bus stops btc is located in kecamatan bekasi timur , in the city of bekasi the rate of population growth in the year 2019 as much as 1.4 %. Walking is a mode of transportation. All buildings are provided for pedestrians in order to provide services to pedestrians so as to improve the smoothness, safety and comfort of pedestrians. The purpose of this study is to analyze the performance of pedestrian facilities in Bekasi Terminal and BTC bus stops. The method used is conducting direct field surveys and data processing using Microsoft Excel. The results of the author's research include the minimum width of the sidewalk in 2020 and 2025 of 1.5 - 1.6 meters and the service level of pedestrian facilities is classified as A, which means that pedestrians can walk freely, including being able to determine the direction of walking freely, at speed. relatively fast without causing interference between pedestrians. The existing condition of sidewalks in 2020, namely there are several obstacles for pedestrians such as the presence of street vendors, several motorbikes parked carelessly, buying and selling activities in markets close to Bekasi Terminal and limited integration facilities around the place. Planning that the authors do is to increase the width of the sidewalk to 3 meters, arrangement of closed drainage on the shoulder of the road, and the addition of street lighting facilities.